A soft magnetic composite material and preparation method thereof
Through the combination of ultrasonic vibration and electric stirring, nano-scale particles are coated on the surface of soft magnetic powder, solving the problem of high-frequency loss of iron-based soft magnetic composite materials, and achieving the improvement of high-frequency magnetic properties and the reduction of losses. Industrial application.
Patent Information
- Application Number
- CN202311004547.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-10
AI Technical Summary
The prior art is difficult to effectively reduce the high-frequency loss of iron-based soft magnetic composite materials and cannot meet the needs of higher frequency operation.
By combining ultrasonic vibration and electric stirring, nano-scale particles are coated on the surface of soft magnetic powder to form a multi-layered coating structure to reduce high-frequency losses.
It effectively improves the high-frequency magnetic properties of soft magnetic powder, reduces the high-frequency loss of soft magnetic composite materials, and has a simple process and low cost, making it suitable for industrial applications.
Smart Images

Figure CN117198674B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soft magnetic composite material preparation, and in particular to a soft magnetic composite material and a preparation method thereof. Background Art
[0002] As an important component for powering chips, chip inductors have extremely high requirements for size, power loss and DC bias performance. The magnetic properties of chip inductors are usually reflected by the magnetic properties of soft magnetic composite materials.
[0003] Soft magnetic composites (SMCs) are magnetic materials with low coercivity and high magnetic permeability. They are easy to magnetize and demagnetize, and are reflected in the hysteresis loop as being more slender. Their main functions are the conversion and transmission of magnetic conductivity and electromagnetic energy, and they are widely used in various electrical circuits. In particular, with the substantial increase in the demand for power transmission and control of electrical circuits in the EV / green energy transition, and the advent of new communication technologies that have brought about higher operating frequencies and miniaturization requirements, the demand for soft magnetic composite materials and technical processes have been rapidly iterated. Iron-based soft magnetic composites have the advantages of high saturation magnetic induction intensity, low loss, and a wide frequency response range, so they have great application potential in power transmission, electronic technology and communications, and automotive energy fields.
[0004] At present, various methods such as powder metallurgy, hot pressing, plasma sintering, 3D printing, etc. are used to prepare iron-based soft magnetic composite materials, and the most widely used method is powder metallurgy. In the research and application of iron-based soft magnetic composite materials, with the advancement of science and technology, higher performance soft magnetic alloy powders are needed to cope with higher frequency work. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a soft magnetic composite material and a preparation method thereof, which coats nanoscale particles on the surface of soft magnetic powder by combining ultrasonic vibration with electric stirring, thereby effectively reducing the high-frequency loss of the soft magnetic composite material.
[0007] (II) Technical solution
[0008] In order to achieve the above object, the main technical solutions adopted by the present invention include:
[0009] In a first aspect, an embodiment of the present invention provides a method for preparing a soft magnetic composite material.
[0010] A method for preparing a soft magnetic composite material provided in an embodiment of the present invention is characterized in that the method comprises:
[0011] annealing the ferromagnetic powder, placing the ferromagnetic powder and the coupling agent in a first anhydrous ethanol, stirring, separating the ferromagnetic powder and drying;
[0012] placing the nanoparticles in a second anhydrous ethanol, acetone or deionized water, and subjecting the nanoparticles to a first ultrasonic vibration treatment to obtain a nanoparticle solution;
[0013] The dried ferromagnetic powder is placed in the nanoparticle solution, and the nanoparticle solution is subjected to a second ultrasonic vibration treatment, the ultrasonic power is controlled to be 100 to 900 W, the vibration frequency is 1 kHz to 40 kHz, and the solution is stirred with an electric stirring device at a stirring speed of 100 to 2000 rpm during the second ultrasonic vibration treatment, so as to make the nanoparticles adhere to the surface of the ferromagnetic powder, and the ferromagnetic powder is separated from the solution and dried to obtain an iron-based soft magnetic powder;
[0014] The iron-based soft magnetic powder and the binder are placed in an acetone reagent, stirred, and then dried to obtain an iron-based soft magnetic powder with a multi-layer coating structure on the surface;
[0015] The iron-based soft magnetic powder with the multi-layer surface coating structure is pressed into shape, and is subjected to segmented annealing in a protective gas atmosphere to obtain an iron-based soft magnetic composite material.
[0016] Furthermore, the annealing process route of the segmented annealing is: controlling the temperature at 200-400°C and keeping it warm for 30-120 minutes, adjusting the temperature at 400-500°C and keeping it warm for 30-120 minutes, then adjusting the temperature at 500-600°C and keeping it warm for 30-120 minutes, and then adjusting the temperature at 600-900°C and keeping it warm for 30-120 minutes.
[0017] Furthermore, the mass percentages of the ferromagnetic powder, the coupling agent, the nanoparticles, and the binder are: 1: (0.1% to 3%): (0.1% to 4%): (1% to 4%).
[0018] Furthermore, the mass percentage of the iron-based soft magnetic powder and the second anhydrous ethanol is: 1: (5% to 20%);
[0019] The mass percentage of the iron-based soft magnetic powder and the deionized water is: 1: (20% to 200%).
[0020] Furthermore, the nanoparticles are one or more of nano-ferroferric oxide, nano-magnesium oxide, nano-zirconium dioxide, nano-silicon dioxide, nano-cobalt oxide, silicon nitride, boron nitride, titanium dioxide, and aluminum oxide.
[0021] Furthermore, the iron-based soft magnetic powder is at least one of FeSiNbBCu, FeSiCr, FeSiBCrC, FeNi, FeSiB, FeSi, FeSiAl, and carbonyl iron powder.
[0022] Furthermore, the protective gas is at least one of nitrogen, argon, oxygen, hydrogen and air.
[0023] Furthermore, the coupling agent is at least one of KH792, DL602, KH550, and KH570.
[0024] Furthermore, the size of the nanoparticles is 10 to 100 nm.
[0025] In a second aspect, an embodiment of the present invention provides a soft magnetic composite material.
[0026] A soft magnetic composite material provided in an embodiment of the present invention is prepared by the preparation method described in the first aspect above.
[0027] (III) Beneficial effects
[0028] The invention has the beneficial effects of: a soft magnetic composite material and a preparation method thereof proposed by the invention comprises the following steps: annealing ferromagnetic powder and placing the ferromagnetic powder with a coupling agent in anhydrous ethanol for stirring, separating the ferromagnetic powder and drying it; placing nanoparticles in anhydrous ethanol, acetone or deionized water, subjecting the nanoparticles to a first ultrasonic vibration treatment to obtain a nanoparticle solution; placing the dried ferromagnetic powder in the nanoparticle solution, subjecting the nanoparticle solution to a second ultrasonic vibration treatment, controlling the ultrasonic power to be 100 to 900 W, the vibration frequency to be 1 kHz to 40 kHz, and The solution is stirred by an electric stirring device at a stirring speed of 100-2000 revolutions per minute at the same time as the second ultrasonic vibration treatment; the nanoparticles are attached to the surface of the ferromagnetic powder, and the ferromagnetic powder is separated from the solution and dried to obtain an iron-based soft magnetic powder; the iron-based soft magnetic powder and the binder are placed in an acetone reagent, stirred, and then dried to obtain an iron-based soft magnetic powder with a surface multi-layer coating structure; the iron-based soft magnetic powder with a surface multi-layer coating structure is pressed into shape, and after heat treatment, segmented annealing is performed in a protective gas protective atmosphere to obtain an iron-based soft magnetic composite material.
[0029] This method coats nano-scale particles on the surface of soft magnetic powder by combining ultrasonic vibration with electric stirring. The coating layer formed by ultrasonic vibration treatment can effectively reduce the power loss of soft magnetic composite materials and further improve the high-frequency magnetic properties of soft magnetic powder. In addition, the coating reagent is a common chemical product available on the market, with low production cost, simple coating process, and no special equipment and experimental environment are required. The experimental conditions are simple and the process steps are few, which is suitable for actual industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention is a process flow chart of a method for preparing a soft magnetic composite material. DETAILED DESCRIPTION
[0031] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.
[0032] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0033] In these embodiments, unless otherwise specified, the parts and percentages are all measured by mass. "Parts by mass" refers to the basic unit of measurement representing the mass ratio relationship of multiple components. 1 part can represent any unit mass, such as 1g, 3.527g, etc. If we say that the mass parts of component A are a parts and the mass parts of component B are b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass parts of all components is not limited to 100 parts. "And / or" is used to indicate that one or both of the situations described may occur, for example, A and / or B include (A and B) and (A or B).
[0034] refer to Figure 1 In a first aspect, an embodiment of the present invention provides a method for preparing a soft magnetic composite material.
[0035] An embodiment of the present invention provides a method for preparing a soft magnetic composite material, wherein the method comprises:
[0036] Step 1: annealing the ferromagnetic powder, placing the ferromagnetic powder and the coupling agent in a first anhydrous ethanol, stirring, separating the ferromagnetic powder and drying;
[0037] In the technical solution, the mass percentages of ferromagnetic powder, coupling agent, nanoparticles and binder are: 1: (0.1% to 3%): (0.1% to 4%): (1% to 4%).
[0038] In the technical solution, the nanoparticles are one or more of nano-ferroferric oxide, nano-magnesium oxide, nano-zirconium dioxide, nano-silicon dioxide, nano-cobalt oxide, silicon nitride, boron nitride, titanium dioxide, and aluminum oxide.
[0039] In the present technical solution, the iron-based soft magnetic powder is at least one of FeSiNbBCu, FeSiCr, FeSiBCrC, FeNi, FeSiB, FeSi, FeSiAl, and carbonyl iron powder.
[0040] In the technical solution, the coupling agent is at least one of KH792, DL602, KH550, and KH570.
[0041] Step 2: placing the nanoparticles in a second anhydrous ethanol, acetone or deionized water, and subjecting the nanoparticles to a first ultrasonic vibration treatment to obtain a nanoparticle solution;
[0042] In the technical solution, the mass percentage of the iron-based soft magnetic powder and the second anhydrous ethanol is: 1: (5% to 20%);
[0043] The mass percentage of the iron-based soft magnetic powder and deionized water is: 1: (20% to 200%).
[0044] It should be noted that the first ultrasonic vibration treatment can make the nanoparticles completely dispersed in the solution.
[0045] In the present technical solution, the size of the nanoparticles is 10 to 100 nm.
[0046] Step 3: placing the dried ferromagnetic powder in a nanoparticle solution, subjecting the nanoparticle solution to a second ultrasonic vibration treatment, controlling the ultrasonic power to 100 to 900 W, the vibration frequency to 1 kHz to 40 kHz, and using an electric stirring device to stir the solution at a stirring speed of 100 to 2000 rpm during the second ultrasonic vibration treatment; the method is used to make the nanoparticles adhere to the surface of the ferromagnetic powder, separate the ferromagnetic powder from the solution and dry it, and obtain an iron-based soft magnetic powder;
[0047] It should be noted that, by stirring the solution with an electric stirring device at a stirring speed of 100-2000 rpm while subjecting the solution to ultrasonic vibration treatment, the ferromagnetic particles can be prevented from settling at the bottom of the solution, and the nanoparticles can be evenly attached to the surface of the ferromagnetic powder through stirring.
[0048] Step 4: placing the iron-based soft magnetic powder and the binder in an acetone reagent, stirring and drying, to obtain an iron-based soft magnetic powder with a multi-layer coating structure on the surface;
[0049] For example, the iron-based soft magnetic powder and the binder may be placed in an acetone reagent and stirred for 5 to 20 minutes, and the magnetic powder may be dried.
[0050] Step 5: Pressing the iron-based soft magnetic powder with a multi-layer surface coating structure into a shape, and performing segmented annealing in a protective gas atmosphere to obtain an iron-based soft magnetic composite material.
[0051] In the present technical scheme, the annealing process route of the staged annealing is: control the temperature at 200-400°C and keep it warm for 30-120 minutes, adjust the temperature at 400-500°C and keep it warm for 30-120 minutes, then adjust the temperature at 500-600°C and keep it warm for 30-120 minutes, and then adjust the temperature at 600-900°C and keep it warm for 30-120 minutes.
[0052] In the present technical solution, the protective gas is at least one of high-purity nitrogen, high-purity argon, high-purity oxygen, high-purity hydrogen, and air.
[0053] The preparation method of a soft magnetic composite material mentioned in the present application is to coat nano-scale particles on the surface of soft magnetic powder by ultrasonic vibration. The coating layer formed by ultrasonic vibration treatment can effectively improve the high-frequency magnetic properties of the soft magnetic powder, thereby effectively reducing the high-frequency loss of the soft magnetic composite material. In addition, the coating agent is a common chemical product available on the market, with low production cost, and the coating process is simple, and no special equipment and experimental environment are required. The experimental conditions are simple and the process steps are few, which is suitable for actual industrial applications.
[0054] In a second aspect, an embodiment of the present invention provides a soft magnetic composite material.
[0055] A soft magnetic composite material provided in an embodiment of the present invention is prepared by the preparation method of the first aspect. The soft magnetic composite material is prepared by the preparation method of the first aspect, and includes all the beneficial effects mentioned in the first aspect, which will not be described in detail here.
[0056] In order to better understand the above technical scheme, exemplary embodiments of the present invention will be described in more detail below. It should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a clearer and more thorough understanding of the present invention, and to be able to fully convey the scope of the present invention to those skilled in the art.
[0057] Example 1
[0058] Step S1: FeNi magnetic powder and 0.5 wt % coupling agent are placed in 8 wt % anhydrous ethanol and stirred for 20 min, then the magnetic powder is separated from the liquid and dried.
[0059] Step S2: The FeNi magnetic powder and 0.5wt% nano zirconium dioxide in step S1 are placed in 100wt% anhydrous ethanol, and vibrated in an ultrasonic device for 20 minutes, with the power set to 500W and the frequency set to 20kHz, and the solution is stirred using an electric stirring device during the ultrasonic vibration treatment, with the stirring speed set to 500 rpm. The magnetic powder is then separated from the solution and dried to obtain a soft magnetic powder with nanoparticles coated on the surface.
[0060] Step S3: The FeNi magnetic powder and 2 wt % modified silicone resin in step S2 are placed in acetone reagent and stirred for 20 min respectively, and the magnetic powder is dried to obtain FeNi magnetic powder with a multi-layer coating structure on the surface.
[0061] Step S4: The FeNi magnetic powder with a multi-layer surface coating structure in step S3 is pressed and heat treated to obtain an iron-based soft magnetic composite material. The molding pressure is set to 1500 MPa, and the annealing process route is first kept at 300°C for 60 minutes, then kept at 450°C for 60 minutes, then kept at 600°C for 30 minutes, and then kept at 700°C for 120 minutes.
[0062] Example 2
[0063] The present embodiment is different from the embodiment 1 in that the content of nano zirconium dioxide in step S2 is 1 wt %.
[0064] Example 3
[0065] The present embodiment is different from the embodiment 1 in that the content of nano zirconium dioxide in step S2 is 1.5 wt %.
[0066] Example 4
[0067] In this embodiment, the feature different from that of Embodiment 1 is that the content of nano zirconium dioxide in step S2 is 2 wt %.
[0068] Comparative Example 1
[0069] Step S1: FeNi magnetic powder and 0.5 wt % coupling agent are placed in 8 wt % anhydrous ethanol and stirred for 20 min, then the magnetic powder is separated from the liquid and dried.
[0070] Step S2: The FeNi magnetic powder and 2 wt % modified silicone resin in step S1 are placed in acetone reagent and stirred for 20 min respectively, and the magnetic powder is dried to obtain FeNi magnetic powder with a multi-layer coating structure on the surface.
[0071] Step S3: The FeNi magnetic powder with a multi-layer surface coating structure in step S2 is pressed and heat treated to obtain an iron-based soft magnetic composite material. The molding pressure is set to 1500 MPa, and the annealing process route is first kept at 300°C for 60 minutes, then kept at 450°C for 60 minutes, then kept at 600°C for 30 minutes, and then kept at 700°C for 120 minutes.
[0072] Among them, the loss and magnetic permeability of the soft magnetic composite materials prepared in Examples 1 to 4 and Comparative Example 1 are as follows:
[0073] As shown in Table 1.
[0074]
[0075] Table 1
[0076] Example 5
[0077] Step S1: FeSiNbBCu magnetic powder and 1 wt% coupling agent are placed in 10 wt% anhydrous ethanol and stirred for 20 minutes, then the magnetic powder is separated from the solution and dried.
[0078] Step S2: The FeSiNbBCu magnetic powder and 0.2%wt% nano-magnesium oxide in step S1 are placed in 100wt% deionized water at a temperature of 25°C, and vibrated in an ultrasonic device for 20 minutes, with the power set to 400W and the frequency set to 20kHz, and the solution is stirred using an electric stirring device while the ultrasonic vibration treatment is being carried out, with the stirring speed set to 500 rpm. The magnetic powder is then separated from the liquid and dried to obtain the FeSiNbBCu magnetic powder having a coupling agent coating layer and a nano-magnesium oxide coating layer.
[0079] Step S3: The FeSiNbBCu magnetic powder and 3 wt % modified silicone resin in step S2 are placed in acetone reagent respectively, stirred for 10 min and the magnetic powder is dried to obtain FeSiNbBCu magnetic powder with a multi-layer coating structure on the surface.
[0080] Step S4: The FeSiNbBCu magnetic powder with a multi-layer surface coating structure in step S3 is pressed into shape and heat treated to obtain an iron-based soft magnetic composite material. The molding pressure is set to 700 MPa, and the annealing process route is to keep the temperature at 200° C. for 100 minutes.
[0081] Example 6
[0082] The feature of this embodiment that is different from that of Embodiment 5 is that the amount of nano magnesium oxide used is 0.4 wt %.
[0083] Example 7
[0084] In this embodiment, the difference from Example 5 is that the amount of nano magnesium oxide used is 0.6wt%.
[0085] Example 8
[0086] The feature of this embodiment that is different from that of Embodiment 5 is that the amount of nano magnesium oxide used is 0.8 wt %.
[0087] Example 9
[0088] The feature of this embodiment that is different from that of Embodiment 5 is that the amount of nano magnesium oxide used is 1 wt %.
[0089] Comparative Example 2
[0090] Step S1: FeSiNbBCu magnetic powder and 1 wt% coupling agent are placed in 10 wt% anhydrous ethanol and stirred for 20 minutes, then the magnetic powder is separated from the solution and dried.
[0091] Step S2: The FeSiNbBCu magnetic powder and 3 wt % modified silicone resin in step S1 are placed in acetone reagent respectively, stirred for 10 min and the magnetic powder is dried to obtain FeSiNbBCu magnetic powder with a multi-layer coating structure on the surface.
[0092] Step S3: The FeSiNbBCu magnetic powder with a multi-layer surface coating structure in step S3 is pressed into shape and heat treated to obtain an iron-based soft magnetic composite material. The molding pressure is set to 700 MPa, and the annealing process route is to keep the temperature at 200° C. for 100 minutes.
[0093] Among them, the loss and magnetic permeability of the soft magnetic composite materials prepared in Examples 5 to 9 and Comparative Example 2 are as follows:
[0094] As shown in Table 2.
[0095]
[0096] Table 2
[0097] Example 10
[0098] Step S1: FeSiNbBCu magnetic powder and 1 wt% coupling agent are placed in 10 wt% anhydrous ethanol and stirred for 10 min, and then magnetically separated and dried.
[0099] Step S2: The FeSiNbBCu magnetic powder and 0.8wt% nano-magnesium oxide in step S1 are placed in 100wt% deionized water at a temperature of 25°C, and the solution is vibrated by an ultrasonic device, wherein the power of the ultrasonic vibration treatment is set to 100W, and the solution is stirred by an electric stirring device during the ultrasonic vibration treatment, and the stirring speed is set to 500 rpm. Then, the magnetic powder is separated from the solution and the magnetic powder is dried to obtain FeSiNbBCu magnetic powder having a coupling agent coating layer and a nano-magnesium oxide coating layer.
[0100] Step S3: The FeSiNbBCu magnetic powder and 3 wt % modified silicone resin in step S2 are placed in acetone reagent respectively, stirred for 10 min and the magnetic powder is dried to obtain FeSiNbBCu magnetic powder with a multi-layer coating structure on the surface.
[0101] Step S4: The FeSiNbBCu magnetic powder with a multi-layer surface coating structure in step S3 is pressed into shape and heat treated to obtain an iron-based soft magnetic composite material. The molding pressure is set to 700 MPa, and the annealing process route is to keep the temperature at 200° C. for 100 minutes.
[0102] Embodiment 11
[0103] In this embodiment, the feature different from that of Embodiment 10 is that the power of the ultrasonic vibration treatment is set to 300W.
[0104] Example 12
[0105] In this embodiment, the feature different from that of Embodiment 10 is that the power of the ultrasonic vibration treatment is set to 400W.
[0106] Embodiment 13
[0107] In this embodiment, the feature different from that of Embodiment 10 is that the power of the ultrasonic vibration treatment is set to 600W.
[0108] Embodiment 14
[0109] In this embodiment, the feature different from that of Embodiment 10 is that the power of the ultrasonic vibration treatment is set to 900W.
[0110] Comparative Example 3
[0111] Step S1: FeSiNbBCu magnetic powder and 1 wt% coupling agent are placed in 10 wt% anhydrous ethanol and stirred for 10 min, and then magnetically separated and dried.
[0112] Step S2: Place the FeSiNbBCu magnetic powder and 0.8 wt% nano-magnesium oxide in 100 wt% deionized water at 25°C and stir for 10 minutes. Then separate the magnetic powder from the solution and dry the magnetic powder to obtain FeSiNbBCu magnetic powder with a coupling agent coating layer and a nano-magnesium oxide coating layer.
[0113] Step S3: The FeSiNbBCu magnetic powder and 3 wt % modified silicone resin in step S2 are placed in acetone reagent respectively, stirred for 10 min and the magnetic powder is dried to obtain FeSiNbBCu magnetic powder with a multi-layer coating structure on the surface.
[0114] Step S4: The FeSiNbBCu magnetic powder with a multi-layer surface coating structure in step S3 is pressed into shape and heat treated to obtain an iron-based soft magnetic composite material. The molding pressure is set to 700 MPa, and the annealing process route is to keep the temperature at 200° C. for 100 minutes.
[0115] Comparative Example 4
[0116] Step S1: FeSiNbBCu magnetic powder and 1 wt% coupling agent are placed in 10 wt% anhydrous ethanol and stirred for 10 min, and then magnetically separated and dried.
[0117] Step S2: The FeSiNbBCu magnetic powder and 0.8wt% nano-magnesium oxide in step S1 are placed in 100wt% deionized water at a temperature of 25°C, and the solution is vibrated by an ultrasonic device, wherein the power of the ultrasonic vibration treatment is set to 400 W. Then, the magnetic powder is separated from the solution and the magnetic powder is dried to obtain FeSiNbBCu magnetic powder having a coupling agent coating layer and a nano-magnesium oxide coating layer.
[0118] Step S3: The FeSiNbBCu magnetic powder and 3 wt % modified silicone resin in step S2 are placed in acetone reagent respectively, stirred for 10 min and the magnetic powder is dried to obtain FeSiNbBCu magnetic powder with a multi-layer coating structure on the surface.
[0119] Step S4: The FeSiNbBCu magnetic powder with a multi-layer surface coating structure in step S3 is pressed into shape and heat treated to obtain an iron-based soft magnetic composite material. The molding pressure is set to 700 MPa, and the annealing process route is to keep the temperature at 200° C. for 100 minutes.
[0120] Among them, the loss and magnetic permeability of the soft magnetic composite materials prepared in Examples 10 to 14 and Comparative Examples 3 and 4 are shown in Table 3.
[0121]
[0122] Table 3
[0123] In the description of the present invention, each embodiment focuses on the differences from other embodiments, and the same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part description.
[0124] In the description of the present invention, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically limited. Moreover, the term "includes", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements not clearly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements limited by the sentence "comprising one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements.
[0125] In the present invention, unless otherwise clearly specified and limited, when a first feature is “on” or “below” a second feature, it may be that the first and second features are in direct contact, or that the first and second features are in indirect contact through an intermediate medium. Moreover, when a first feature is “above”, “above” or “above” a second feature, it may be that the first feature is directly above or obliquely above the second feature, or it may simply mean that the first feature is higher in level than the second feature. When a first feature is “below”, “below” or “below” a second feature, it may be that the first feature is directly below or obliquely below the second feature, or it may simply mean that the first feature is lower in level than the second feature.
[0126] In the description of this specification, the description of the terms "one embodiment", "some embodiments", "embodiment", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0127] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may alter, modify, replace and modify the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a soft magnetic composite material, characterized in that: The method comprises: annealing the ferromagnetic powder, placing the ferromagnetic powder and the coupling agent in a first anhydrous ethanol, stirring, separating the ferromagnetic powder and drying; placing the nanoparticles in a second anhydrous ethanol, acetone or deionized water, and subjecting the nanoparticles to a first ultrasonic vibration treatment to obtain a nanoparticle solution; The dried ferromagnetic powder is placed in the nanoparticle solution, and the nanoparticle solution is subjected to a second ultrasonic vibration treatment, the ultrasonic power is controlled to be 100 to 900 W, the vibration frequency is 1 kHz to 40 kHz, and an electric stirring device is used to stir the solution at a stirring speed of 100 to 2000 rpm during the second ultrasonic vibration treatment, so as to make the nanoparticles adhere to the surface of the ferromagnetic powder, and the ferromagnetic powder is separated from the solution and dried to obtain an iron-based soft magnetic powder; The iron-based soft magnetic powder and the binder are placed in an acetone reagent, stirred, and then dried to obtain an iron-based soft magnetic powder with a multi-layer coating structure on the surface; The iron-based soft magnetic powder with a multi-layer surface coating structure is pressed into a shape, and annealed in sections in a protective gas atmosphere to obtain an iron-based soft magnetic composite material; The annealing process route of the stepwise annealing is: controlling the temperature at 200-400°C and keeping it warm for 30-120 minutes, adjusting the temperature at 400-500°C and keeping it warm for 30-120 minutes, adjusting the temperature at 500-600°C and keeping it warm for 30-120 minutes, and further adjusting the temperature at 600-900°C and keeping it warm for 30-120 minutes; The mass percentages of the ferromagnetic powder, the coupling agent, the nanoparticles, and the binder are: 1: (0.1% to 3%): (0.1% to 4%): (1% to 4%); The mass percentage of the iron-based soft magnetic powder and the second anhydrous ethanol is: 1: (5% to 20%); The mass percentage of the iron-based soft magnetic powder and the deionized water is: 1: (20% to 200%).
2. The method for preparing a soft magnetic composite material according to claim 1, characterized in that: The nanoparticles are one or more of nano-ferroferric oxide, nano-magnesium oxide, nano-zirconium dioxide, nano-silicon dioxide, nano-cobalt oxide, silicon nitride, boron nitride, titanium dioxide, and aluminum oxide.
3. The method for preparing a soft magnetic composite material according to claim 1, characterized in that: The iron-based soft magnetic powder is at least one of FeSiNbBCu, FeSiCr, FeSiBCrC, FeNi, FeSiB, FeSi, FeSiAl, and carbonyl iron powder.
4. The method for preparing a soft magnetic composite material according to claim 1, characterized in that: The protective gas is at least one of nitrogen, argon, oxygen, hydrogen and air.
5. The method for preparing a soft magnetic composite material according to claim 1, characterized in that: The coupling agent is at least one of KH792, DL602, KH550 and KH570.
6. The method for preparing a soft magnetic composite material according to claim 1, characterized in that: The size of the nanoparticles is 10 to 100 nm.
7. A soft magnetic composite material prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Insulating binder for coating amorphous and nanocrystalline magnetic powder and coating method
CN105261436A
Magnetic powder surface gradient coating structure and coating method and soft magnetic composite
CN110405201A
Organic-inorganic composite coated iron-based soft magnetic composite material and preparation method thereof
CN116137203A